Analysis of Henry Ford’s contribution to production and management - Tomac, Nikola (Array, 2019)
Henry Ford is widely known as the car constructor, the founder of the Ford Motor Company, the pioneer of mass production and the inventor of the moving assembly line, which many consider as the world’s greatest contribution to manufacturing. In 1908, Ford started production of the Ford Model T, which has become one of the most successful automobile in automotive history. But his contribution far surpasses these excellent accomplishments. What are not well known are Ford’s contributions to the just-in-time production, product platforming, mass customization, vertical integration, designs for maintainability, ergonomic considerations, employee management and other features of the manufacture. The Ford’s production system has become the characteristic American mode of production widespread all over the world.